(untitled) (Palíndromo, 2018)
The aim of the present study is to enlight the concepts “The Sublime and The Grotesque” according to the historic period called Romantic, and correlations between them. These research is based on the philosophy of Edmund Burk, Friedrich Schiller and Victor Hugo, who were deeply involved in the historical moment and approached the theme thoroughly.